Incidence and Risk Factors of Surgical Site Infection Among Patients Undergoing Cesarean Section - Hussein Jasim, Hanan; Syed Sulaiman, Syed Azhar; Hayat Khan, Amer; Thanoon Dawood, Omar; Abdulameer, Aseel Hadi; Usha, R (Libertas Academica, 2017)
Background: Wound infections constitute a significant problem in surgical procedures. In cesarean sections (CS), this is particularly important as a wound infection not only results in increased morbidity but also has far-reaching implications by way of pelvic organ disease, disturbance of the bonding process between mother and baby in the puerperium, and a longer hospital stay with its inherent problems. Objective: This study was conducted with the aim to determine the incidence and risk factor associated with surgical site infection (SSI) following cesarean section. Methodology: A retrospective cross-sectional study was conducted for 400 women undergoing cesarean section procedures during an 18-month period from January 2013 to June 2014 at Hospital Pulau Pinang, Malaysia. Patients’ socio-demographic, clinical data and incidence of SSI following the CS were noted using a standardized data collection form. SPSS v 21 was used for data analysis. Resu lts : In total, 18.8% of the study participants developed SSI. Multivariate logistic regression analysis identified the following: higher body mass index (≥30 kg/m2) (odds ratio [OR]: 0.555; 95% confidence interval [CI] = 0.313-0.985, P = .044), increase in the blood loss during surgery (≥500 mL) (OR: 0.757; 95% CI = 0.423-1.354, P = .034), prolonged hospital stay (≥4 days) (OR: 0.439; 95% CI = 0.260-0.740, P = .002), spinal anesthesia (OR: 1.543; 95% CI = 1.230-1.937, P = .021), breech baby presentation (OR:2.927 95% CI = 1.020-8.400, P = .046), and intrathecal analgesia (OR:1.567; 95% CI = 1.246-1.970, P = .001) had statistically significant association with incidence of SSI. Conclusions: Surgical site infections are common among women undergoing CS at Hospital Pulau Pinang. Special attention and enhanced clinical management of patients with identified risk factors for developing SSI may decrease its incidence.